Tuberculosis Recurrence: Associated Factors in an Epidemiological Surveillance Group of São Paulo - Isabela Cristina Rodrigues; Silvia Helena Figueiredo Vendramini; Maria Amélia Zanon Ponce; Antônio Ruffino-Neto; Nilza Gomes de Souza; Francisco Chiaravalloti Neto; Maria de Lourdes Sperli Geraldes Santos; Anneliese Domingues Wysocki (Universidade Federal de Goias, 2017)
Analyze the factors related to cases of tuberculosis (TB) recurrence in reports of the Epidemiological Surveillance Group XXIX/São José do Rio Preto/SP. This is a case-control study that analyzes pulmonary TB reports in the period between 1996 and 2014. Cases were reports of "Recurrence" and control: reports classified as "New" case and with "Healed" outcome. Odds ratio and multivariate analysis with 95% confidence interval were used to analyze the data. The variables of gender and adverse outcome in the 7th month remained significantly associated with recurrence. Males showed 1.8 times greater risk (p = 0.0551) and individuals who obtained an adverse outcome in the 7th month of treatment were 4.6 times more likely to recur (p = 0.0000). We found two factors associated with recurrence: male gender and adverse treatment outcome, which shows the need to assess the quality of the care provided.